Correct System Design Symposium in Honor of Ernst-Rüdiger Olderog on the Occasion of His 60th Birthday, Oldenburg, Germany, September 8-9, 2015, Proceedings - Meyer, Roland; Platzer, André; Wehrheim, Heike (Theoretical Computer Science and General Issues, 2015)
This book is dedicated to Professor Ernst--Rüdiger Olderog on the occasion of his 60th birthday. This volume is a reflection on Professor Olderog's contributions to the scientific community. It provides a sample of research ideas that have been influenced directly by Ernst-Rüdiger Olderog's work. After a laudatio section that provides a brief overview of Ernst-Rüdiger Olderog's research, the book is comprised of five parts with scientific papers written by colleagues and collaborators of Professor Olderog. The papers address semantics, process algebras, logics for verification, program analysis, and synthesis approaches.